Revisiting the jurisdiction of Moscow Patriarchate (Unapproved draft decree of 1950) - Kostryukov, Andrey Aleksandrovich (The Quarterly Journal of St. Philaret's Institute, 2022)
A draft resolution is being introduced into scientific circulation, which was to be adopted by the Holy Synod of the Russian Orthodox Church in 1950. The ruling could have a significant impact on the church situation in the world and give the supporters of the Moscow Patriarchate new arguments against the North American Metropolis, the Western European Exarchate and the Russian Church Abroad. Should the document had been adopted and the Moscow Patriarchate supported by the state, this document could have helped it get real estate abroad (including the Alexander Nevsky Cathedral on Rue Daru in Paris) or at least part of them. The document assumed subordination to the Patriarch of Moscow of all Russian dioceses and parishes. Against the background of the communist state’s desire to use the Moscow Patriarchate in its foreign policy activities, the document, it would seem, should have received approval from the Council for the Affairs of the Russian Orthodox Church. However, no such statement followed. There were several reasons. First of all, the state did not want to interfere in property lawsuits around the world, which required large financial investments. Also by 1950, the Soviet state became disillusioned with the foreign policy role of the Moscow Patriarchate and launched a new offensive against it. The strengthening of the Church in the circumstances of that time was not beneficial to the state.